Common Volatility Trends in the Central and Eastern European Currencies and the Euro - Pramor, Marcus (IMF Working Papers; Working Paper ;, 2006)
How much convergence has been achieved between Central and Eastern European (CEE) economies and the eurozone? We explore this question by comparing long-run volatility trends in CEE currencies and the euro. We find that these trends are closely correlated, pointing to convergence in the economic and financial structures of these economies. Nonetheless, the degree of commonality remains weaker than what had been found for major European currencies before the introduction of the euro. Spillovers of volatility across regional markets appear to have diminished over time, with the exception of the Hungarian forint, which remains a source of volatility shocks to regional currencies.